Case Report: Treatment for steroid-refractory immune-related myocarditis with tofacitinib - Xing, Qian; Zhang, Zhongwei; Zhu, Biao; Lin, Qionghua; Shen, Lihua; Li, Fangfang; Xia, Zhili; Zhao, Zhiyong (Frontiers in Immunology, 2022)
Introduction Immune therapy has ushered in a new era of tumor treatment, at the expense of immune-related adverse events, including rare but fatal adverse cardiovascular events, such as myocarditis. Steroids remain the cornerstone of therapy for immune-related myocarditis, with no clear consensus on additional immunosuppressive treatment for steroid-refractory cases yet. Case report Here, we report a patient with stage IV nasopharyngeal carcinoma who developed immune-related myocarditis in the fourth course of therapy with immune checkpoint inhibitors. The patient presented with precordial discomfort with elevation of cardiac enzymes and interleukin-6, atypical electrocardiographic abnormalities, and reduced left ventricular ejection fraction. Coronary computed tomography angiography excluded the possibility of acute coronary syndrome. The therapy with tofacitinib targeting the Janus kinase-signal transducer and activator of transcription signal pathway was successfully conducted, since there was no significant improvement in troponin under high-dose steroid and intravenous immunoglobulin treatment. The patient recovered without major adverse cardiac events during hospitalization. Discussion The safety and efficacy of tofacitinib in a patient with steroid-refractory immune-related myocarditis were investigated, hoping to provide a basis for prospective therapeutic strategies. Tofacitinib led to remarkable remissions in primary autoimmune disease by blocking the inflammatory cascade, indicating its potential therapeutic use in immune-related adverse events.